Predesign Phase-Model of Consequent Developing and Managing Architectural Projects and its Possible Application in Legal Framework - Starhinja Trpevski; Dimitar Papasterevski (9th UBT International Conference on Architecture and Spatial Planning, Lipjan, Kosovo, 2020)
Abstract. The transformation and development of the conceptual idea (conceptual architectural solution) in the preliminary and main architectural project design documentation for construction is successively moving from something less defined (relatively) to something comprehensive, precise and clearly defined (materialized). In this paper is analyzed process of selected consequential and inverse research and decision-making steps which resolved architectural and other problems in the development of the process. Considering the fact that the development of architectural projects is a process of permanent consequential and inverse research on aesthetic shaping and material aspects of the architectural product, architectural construction, a key thesis of this research is that creating a good and meaningful architecture can be established and achieved based on the rule of epistemology of complex scientific knowledge, highly developed modes of operation, experiential skills and capacities to systematically explore architectural problems.
Keywords: Project process1, Architectural solution2, Basic architectural design3, Project documentation4